Muscle and cerebral oxygenation during exercise in athletes with exercise-induced hypoxemia: A comparison between sea level and acute moderate hypoxia - Raberin, A.; Meric, H.; Mucci, P.; Lopez Ayerbe, J.; Durand, F. (European Journal of Sport Science, 2020)
The objective of the present study was to evaluate the influence of exercise-induced hypoxemia (EIH) on muscle and cerebral oxygenation responses during maximal exercise in normoxia and in acute moderate hypoxia (fraction of inspired oxygen: 15.3%, 2400 m). EIH was defined as a drop in hemoglobin saturation of at least 4% for at least three consecutive minutes during maximal exercise at sea level. Twenty-five athletes performed incremental treadmill tests to assess maximal oxygen consumption (VO2max) in normoxia and in hypoxia. Oxygenation of the vastus lateralis muscle and the left prefrontal cortex of the brain was monitored using near-infrared spectroscopy. During the normoxic test, 15 athletes exhibited EIH; they displayed a larger change in muscle levels of oxyhemoglobin (DeltaO2Hb) (p = 0.04) and a greater change in cerebral levels of deoxyhemoglobin (DeltaHHb) (p = 0.02) than athletes without EIH (NEIH group). During the hypoxic test, muscle DeltaO2Hb was lower in the EIH group than in the NEIH group (p = 0.03). At VO2max, hypoxia was associated with a smaller cerebral DeltaO2Hb in both groups, and a greater cerebral DeltaHHb compared to normoxia in the NEIH group only (p = 0.02). No intergroup differences in changes in muscle oxygenation were observed. The severity of O2 arterial desaturation was negatively correlated with changes in total muscle hemoglobin in normoxia (r = -0.48, p = 0.01), and positively correlated with the cerebral DeltaHHb in normoxia (r = 0.45, p = 0.02). The occurrence of EIH at sea level was associated with specific muscle and cerebral oxygenation responses to exercise under both normoxia and moderate hypoxia.